Spatial and seasonal variability of tap water disinfection by-products within distribution pipe networks - Andra, Syam S.; Vamvakousis, Vasilis; Kargaki, Sophia; Stephanou, Euripides G.; Makris, Konstantinos C.; Christophi, Costas A.; Charisiadis, Pantelis; Skarlatos, Dimitrios (My University, 2015)
Gradually-changing shocks associated with potable water quality deficiencies are anticipated for urban drinking-water distribution systems (UDWDS). The impact of structural UDWDS features such as, the number of pipe leaking incidences on the formation of water trihalomethanes (THM) at the geocoded household level has never been studied before. The objectives were to: (i) characterize the distribution of water THM concentrations in households from two district-metered areas (DMAs) with contrasting UDWDS characteristics sampled in two seasons (summer and winter), and (ii) assess the within- and between-household, spatial variability of water THM accounting for UDWDS characteristics (household distance from chlorination tank and service pipe leaking incidences). A total of 383 tap water samples were collected from 193 households located in two DMAs within the UDWDS of Nicosia city, Cyprus, and analyzed for the four THM species. The higher intraclass correlation coefficient (ICC) values for water tribromomethane (TBM) (0.75) followed by trichloromethane (0.42) suggested that the two DMAs differed with respect to these analytes. On the other hand, the low ICC values for total THM levels between the two DMAs suggested a large variance between households. The effect of households nested under each DMA remained significant (p < 0.05) for TBM (not for the rest of the THM species) in the multivariate mixed-effect models, even after inclusion of pipe network characteristics. Our results could find use by water utilities in overcoming techno-economic difficulties associated with the large spatiotemporal variability of THM, while accounting for the influence of UDWDS features at points of water use.
Keywords: Disinfectant; Disinfection by-products; Drinking water distribution system; Spatial and temporal trends; Trihalomethanes; Within- and between-variability